Liquidity, Stock Price, Financial Performance, and Stock Returns Before and After the Acquisition in Raw Goods Sector Companies - Murni, Nur Suci I Mei; Permata, Elisa Ihrama Intan (Golden Ratio of Finance Management, 2025)
The purpose of this study is to compare liquidity, stock price, financial performance, and stock returns between three years before and three years after the company made an acquisition. The indicators used in this study are current ratio (CR), earnings per share (EPS), return on assets (ROA), and stock return (Ri). The research method employed is a mixed-methods approach, combining quantitative and qualitative methods, with secondary data sourced from the company's annual financial statements and existing news reports. The population in this study consisted of companies that made acquisitions during the 2010-2019 period in the raw goods sector, listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling.. The data of this study were analyzed using the Wilcoxon Signed Ranks Test analysis technique with SPSS 26 software. The study's findings indicate that the current ratio, earnings per share, return on assets, and stock return have no significant difference before and after the acquisition.